Cognitive And Affective Image: The Secret Behind The Charm Of Pos Bloc Medan - Oktavia, Monica; Nasution, Muhammad Dharma Tuah Putra (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of cognitive image and affective image on visitor satisfaction at Pos Bloc Medan, a creative tourism destination that combines art spaces with historical colonial buildings. The research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM), analyzed with SmartPLS version 4. The sample consisted of 100 visitors selected through purposive sampling. The results showed that cognitive image had a positive and significant effect on visitor satisfaction (path coefficient = 0.481; t-statistic = 5.981), while affective image also had a positive and significant but smaller effect (path coefficient = 0.230; t-statistic = 3.012). The limitations of this study include the relatively small sample size and the scope being limited to one destination. This study contributes to the literature on destination image and tourist experience management, particularly in the context of cultural and creative tourism destinations in Indonesia. The findings offer practical implications for destination managers to emphasize the importance of improving physical attributes and creating deep emotional experiences to sustainably enhance visitor satisfaction.